When "Time Is Not Your Own": Experiences of Mothering Students During the COVID-19 Pandemic. Issue 2 (May 2023) - LaBrenz, Catherine A.; Robinson, Erica D.; Chakravarty, Sreyashi; Vasquez-Schut, Gladis; Mitschke, Diane B.; Oh, Sehun
As COVID-19 reached pandemic levels in March 2020, schools shifted to remote learning. Student parents in higher education had to adapt to their own remote learning and assume responsibility for childcare and their children's education. Few studies have explored the impact of COVID-19 on mothers who are also full-time students. This study utilized a phenomenological approach to understand the lived experiences of mothering students during the COVID-19 pandemic. Student mothers were recruited from a large, public, Hispanic-serving university in a Southern state. We conducted interviews with 15 student mothers who had at least one child under the age of 18 during the first six months of the pandemic. Three main themes emerged from the analyses: (1) successfully meeting educational requirements; (2) dealing with the mental health impact of the pandemic; and (3) changing the institutional structure. The first theme captured strategies mothering students implemented to ensure their own or their children's educational goals were met. The second theme encompassed how mothers handled the stress caused by the pandemic. The third theme explored ways that mothers resisted gendered expectations and norms around care. Implications for policy and social work practice include changing institutional structures to enhance support for mothering students.